Rehabilitation planning for small tanks in cascades: a methodology based on rapid assessment - Sakthivadivel, Ramaswamy; Fernando, N.; Brewer, J.D. (International Irrigation Management Institute, 1997)
Presents a methodology for planning the rehabilitation and improvement of small-scale irrigation systems within the context of the water basin when information on hydrology and water use is inadequate. The methodology is useful to those undertaking irrigation rehabilitation projects in similar circumstances, and it may also be extended to water resources planning in many other circumstances.